SGStudio: Rapid Semantic Grammar Development for Spoken Language Understanding - Wang, Ye-Yi; Acero, Alex (9th European Conference on Speech Communication and Technology, 2005)
SGStudio (Semantic Grammar Studio) is a grammar authoring tool that facilitates the development of spoken dialog systems and speech enabled applications. It enables regular software developers with little speech/linguistic background to rapidly create quality semantic grammars for automatic speech recognition (ASR) and spoken language understanding (SLU). This paper introduces the framework of the tool as well as the component technologies, including knowledge assisted example-based grammar learning, grammar controls and configurable grammar structures. While the focus of SGStudio is to increase the productivity, experimental results show that it also improves the quality of the grammars.